2015
DOI: 10.1002/pmic.201400441
|View full text |Cite
|
Sign up to set email alerts
|

Version 4.0 of PaxDb: Protein abundance data, integrated across model organisms, tissues, and cell‐lines

Abstract: Protein quantification at proteome-wide scale is an important aim, enabling insights into fundamental cellular biology and serving to constrain experiments and theoretical models. While proteome-wide quantification is not yet fully routine, many datasets approaching proteomewide coverage are becoming available through biophysical and MS techniques. Data of this type can be accessed via a variety of sources, including publication supplements and online data repositories. However, access to the data is still fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
537
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 527 publications
(578 citation statements)
references
References 29 publications
(34 reference statements)
14
537
2
2
Order By: Relevance
“…This evidence confirms initial studies suggesting that Mkk1 could be a stronger Slt2 activator than Mkk2 (Martin et al 2000). The preeminent role of Mkk1 over Mkk2 cannot be attributed to a higher abundance of Mkk1 because evaluation of the data collected at the PaxDb (Wang et al 2015) indicates that, in most studies, Mkk2 cellular protein levels are found to be similar to or even higher than those of Mkk1. Therefore, alternative possibilities must be considered (i.e., different specific activity or distinct subcellular localization).…”
Section: Discussionsupporting
confidence: 74%
“…This evidence confirms initial studies suggesting that Mkk1 could be a stronger Slt2 activator than Mkk2 (Martin et al 2000). The preeminent role of Mkk1 over Mkk2 cannot be attributed to a higher abundance of Mkk1 because evaluation of the data collected at the PaxDb (Wang et al 2015) indicates that, in most studies, Mkk2 cellular protein levels are found to be similar to or even higher than those of Mkk1. Therefore, alternative possibilities must be considered (i.e., different specific activity or distinct subcellular localization).…”
Section: Discussionsupporting
confidence: 74%
“…of protein) in the liver (PaxDb version 4.0) to reduce bias towards abundant proteins (Wang et al, 2015). The phospholipase 2 protein (PLA2G4D) came to the fore.…”
Section: Tap-tagged Dengue Virus and Host-virus Interactionsmentioning
confidence: 99%
“…Its best-studied signaling effects are mediated by the oxidation of thiolates in transcription factors [2], kinases [3,4] and phosphatases [5][6][7][8]. However, whereas the redox active thiolates in these targets react with H 2 O 2 with rate constants in the range of 9−164 M −1 s −1 [5,6,9,1], the cell cytoplasm contains very abundant peroxiredoxins I and II (PrxI, PrxII) [10,11], which react with H 2 O 2 with rate constants in the range of 10 7 -10 8 M −1 s −1 [12,13].…”
Section: Introductionmentioning
confidence: 99%